Strategies for enriching erucic acid from Crambe abyssinica oil by improved Candida antarctica lipase A variants. (April 2019) - Zorn, Katja; Oroz-Guinea, Isabel; Bornscheuer, Uwe T.
Graphical abstract: Highlights: Long chain mono-unsaturated fatty acid enrichment by engineered CAL-A lipase variants. Selective enrichment of erucic acid from both, unmodified Crambe oil triacylglycerides and their ethylester derivatives. Study of the lipase variants capability to retain their hydrolytic selectivity at different reaction temperatures. Upscaling of selective hydrolysis of Crambe oil using CAL-A variants from 12.5 mg range to 1 g. Abstract: Erucic acid (C22:1, Δ13 Z ) is an interesting building block for the oleochemical industry and is abundantly present in Crambe abyssinica seed oil (∼59% of C22:1). For the enrichment of fatty acids (FA), lipases can be employed and we have found in a previous protein engineering study suitable variants of lipase A from Moesziomyces antarcticus (CAL-A) for the enrichment of C22:1 from Crambe oil derived ethyl esters (FAEE). To continue with this task a thorough investigation of the best four variants behaviour when using the natural Crambe oil (TAG) as substrate was performed. CAL-A variants showed to be able to enrich C22:1 up to 80% using both substrates, FAEE and TAG. In particular, CAL-A wild type and the double mutant V238 L/V290 L (V1) proved to be the most suitable biocatalysts, because they displayed the best theoretical recovery yields for C22:1 enriched fractions (60–74%). Further characterization of these lipases concerning their temperature profile showed an optimum at high temperatures (60–75 °C) preserving their selectivity in reactions up to 50 °C. Finally, upscaling of the Crambe oil hydrolysis (from 0.01 g to 1 g) with V1 resulted in an enriched esterified C22:1 fraction of 74%.